The effects of mindfulness‐based interventions on nurses' anxiety and depression: A meta‐analysis - Hui Liu; Luya Kong; Qian Sun; Xiaofeng Ma (Wiley, 2023)
Abstract Objective This meta‐analysis aimed to determine the effect of mindfulness interventions on nurses' levels of depression and anxiety. Design Meta‐analysis of randomised controlled trials. Methods The following Chinese and English databases were searched: PubMed, Embase, Cochrane Library, Web of Science, and China National Knowledge Internet (CNKI). The retrieval period was from database construction to 30 March 2022. Two researchers screened the relevant literature and extracted the data. After a cross‐check, data were input into Stata version 16.0 for meta‐analysis. Results Twelve randomised controlled trials from 2017 to 2021 were included, which involved 807 subjects (405 and 402 in the intervention and control groups, respectively). Meta‐analysis results showed that nurses' anxiety reduced by mindfulness‐based interventions was significantly higher compared to that of the control group (SMD = 0.91, 95% CI: 0.27-1.55, p < 0.05). Furthermore, an 8‐week mindfulness‐based intervention (SMD = 1.43, 95% CI: 0.61-2.24) reduced the level of anxiety significantly more compared to a 4‐week intervention (SMD = 1.03, 95% CI: 0.36-1.71). Mindfulness‐based interventions were better compared to conventional intervention to reduce the level of depression (SMD = 1.02, 95% CI: 0.42-1.61, p < 0.05), and an 8‐week mindfulness intervention (SMD = 1.81, 95% CI: 0.78-2.84) reduced the level of depression significantly more compared to a 4‐week intervention (SMD = 0.82, 95% CI: 0.29-1.35). Since limited studies had interventions longer than 8 weeks, results on longer mindfulness interventions in reducing nurses' anxiety and depression are inconclusive. In conclusion, mindfulness intervention for 8 weeks or less can significantly reduce nurses' anxiety and depression levels. Patient or Public Contribution None.